Kebebasan Perempuan dalam Memilih Calon Suami; Studi Perbandingan Antara Mazhab Syafi’i Dan Hanafi - Asmawi, Nur Ilma; Bakry, Muammar (Universitas Islam Negeri Alauddin Makassar, 2020)
The subject of this paper is how the freedom of women in choosing a potential husband. In general, ideas can be put forward in a society where the pattern of relationship is traditional, marriage is perceived as a social necessity which is part of the inherited social tradition. This study aims to find out how the views of the Shafi'i School and the Hanafi School of Women in choosing a husband. Whether choosing a husband candidate is a woman's absolute right or is there interference from parents. Where cases of matchmaking and the practice of forced marriage by parents of girls are still found in Indonesian society. Mazhab Syafi'i and the Hanafi School have different opinions about women's freedom to choose a husband. The Shafi'i school is of the opinion that a girl who is not yet an adult, in this case, according to him, he can marry the girl even without his permission. According to him, for a widow there must be clear consent from the person concerned. Meanwhile, according to the Hanafi School, the consent of a woman, either a widow or a girl, must be in the marriage and vice versa, if they refuse the marriage contract, it cannot be carried out